2014
DOI: 10.3126/jcmc.v3i4.9555
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study On Morbidities Of Patients Attending Free Health Camp In Sankhejung Vdc Of Ilam District, Nepal

Abstract: Free health camp is an important means to cater health services to the needy people in an underdeveloped country like Nepal with difficult geographical terrain. The objective of this study was to assess the morbidities of patients attending the free health camp in Sankhejung, Ilam. A total of 399 patients visited the health camp and 35.1% of them were males. It was observed that diseases with musculoskeletal system and gastrointestinal system were reported among 24.3% and 25.1% of the attendees respectively. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Similar pattern was observed by Rayamajhi in Nepal, Venkatashivareddy study in Uttarakhand, and Rouf et al in north India where they noticed hypertension was 7%. 8,12,13 In another study by Santosh et al in Srinagar where they found the leading cause of noncommunicable diseases was found to be musculoskeletal system and connective tissue. 10 Gopakrishna et al study result showed that majority of the people had illness affecting the respiratory system, symptoms and signs, musculo-skeletal system and digestive system in the order of the proportion affected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar pattern was observed by Rayamajhi in Nepal, Venkatashivareddy study in Uttarakhand, and Rouf et al in north India where they noticed hypertension was 7%. 8,12,13 In another study by Santosh et al in Srinagar where they found the leading cause of noncommunicable diseases was found to be musculoskeletal system and connective tissue. 10 Gopakrishna et al study result showed that majority of the people had illness affecting the respiratory system, symptoms and signs, musculo-skeletal system and digestive system in the order of the proportion affected.…”
Section: Discussionmentioning
confidence: 99%
“…We found majority of the patients in the productive age group between 16-30 years and is consistent with studies in Tamilnadu, Ghaziabad and in Nepal respectively. [6][7][8] Where as in Sanjay Kini study, above 60 years comprised the highest and Niranjan study in Karnataka found majority (50.6%) were in the age group of 15-45 years, followed by 45-60 years (16%) and 13% were above 60 years of age. 9 In the present study geriatric patients constituted around 9 (7.4%) which is comparably lesser to study by Gopalakrishnan et al and Mane et al 4,6 In the current study, it was found that more than half of the patients were males 68 (55.28%) and females were 55 (44.71%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms associated with the musculoskeletal system (72.6%) were the most common health problem in our study followed by general symptoms (29.3%) and symptoms of the circulatory and respiratory system (27.1%). A study done by Rayamajhi et al [5] among female patients attending free health camp showed that musculoskeletal system was the common system affected, followed by the digestive system, genitourinary system, and respiratory system. In the present study, the top six most common symptoms among female patients were myalgia, low back pain, nasal congestion, headache, knee pain, and abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey, the prevalence of self‐reported musculoskeletal disorders in the country was 14.8% . The prevalence was slightly high (24.3%) in a study conducted in a village development committee of Ilam, a district of Nepal . Although the disease prevalence seems to be high in this country, there are no indices translated in the local language.…”
Section: Introductionmentioning
confidence: 97%